2019
DOI: 10.3390/ijms20174138
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetically Defined Isoforms of Listeria monocytogenes Invasion Factor InlB Differently Activate Intracellular Signaling Pathways and Interact with the Receptor gC1q-R

Abstract: The pathogenic Gram-positive bacterium Listeria monocytogenes has been evolving into a few phylogenetic lineages. Phylogenetically defined substitutions were described in the L. monocytogenes virulence factor InlB, which mediates active invasion into mammalian cells via interactions with surface receptors c-Met and gC1q-R. InlB internalin domain (idInlB) is central to interactions with c-Met. Here we compared activity of purified recombinant idInlB isoforms characteristic for L. monocytogenes phylogenetic line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 67 publications
(118 reference statements)
0
21
0
2
Order By: Relevance
“…Strains with the same deletion, isolated from mushroom production environment, have been identified previously (Muruesan et al, 2015). It has been described that different isoforms of the inlB gene have an impact on signaling pathways and invasiveness of L. monocytogenes (Wałecka-Zacharska et al, 2015;Sobyanin et al, 2017;Chalenko et al, 2019). Of note, differences in the sequences of the inlB gene among strains of wild animals and humans were observed, which may suggest that mutations in this gene may have an impact on the invasiveness of L. monocytogenes (Zaytseva et al, 2007).…”
Section: Discussionmentioning
confidence: 98%
“…Strains with the same deletion, isolated from mushroom production environment, have been identified previously (Muruesan et al, 2015). It has been described that different isoforms of the inlB gene have an impact on signaling pathways and invasiveness of L. monocytogenes (Wałecka-Zacharska et al, 2015;Sobyanin et al, 2017;Chalenko et al, 2019). Of note, differences in the sequences of the inlB gene among strains of wild animals and humans were observed, which may suggest that mutations in this gene may have an impact on the invasiveness of L. monocytogenes (Zaytseva et al, 2007).…”
Section: Discussionmentioning
confidence: 98%
“…These pathogens often use effector proteins to manipulate MAPK pathways and allow the bacteria to establish infection within the host (21). Employing a model of the bloodcerebrospinal fluid barrier based on human choroid plexus epithelial papilloma (HIBCPP) cells, a previous study showed that infection with L. monocytogenes triggers activation of ERK1/2 and p38 signaling, and such cellular response is required for L. monocytogenes infection (22,25). Modulation of MAPK pathway signaling by LLO during L. monocytogenes infection has been described in various host cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…The host receptor of InlA is the epithelial cell receptor E-cadherin [ 43 ]. InlB interacts with the tyrosine kinase c-Met and with the complement system receptor gC1q-R [ 44 , 45 , 46 ]. Interactions between InlA and E-cadherin are of key importance for the efficient crossing of the intestinal barrier [ 47 ].…”
Section: Introductionmentioning
confidence: 99%